Interaction between test-taker characteristics, task facets and l2 oral proficiency test performance - Abu Kassim, Noor Lide; Zubairi, Ainol Madziah (IIUM Press, International Islamic University Malaysia, 2006)
The nature of test-taker characteristics and their impact on second language test performance has drawn a considerable amount of research interest among language testers in the last two decades. this is hardly surprising given the potential influence of test-taker attributes on second language (L2) learning and assessment. however, examining the influence of these attributes on test performance alone is insufficient. There are other elements in the assessment framework which also yield a significant amount of influence on test-taker reactions towards certain tasks and test perfromance. it is, therefore, necessary to further investigate the nature of these other factors in the assessment framework and examine how they relate to test-taker reactions and how they impact test perfromance. in this study, the interaction between three main factors in the assessment framework-test task facets, test-taker personla attributes, and language ability-and their simultaneous effect on oral proficiency test perfromance are examined through the use of structural equation modeling which allows the effects of the different factors in the assessment framework to be directly observed and modeled, and their individual effect on test performance estimated.